The Ministry of Public Input - Lees-Marshment, J. author. aut Link
X, 289 p.
Keywords: As political leaders acknowledge the limits of their power they increasingly integrate constructive input from inside and outside government into their decision-making. A Ministry or Commission of Public Input is necessary to collect, process and communicate input more effectively and politicians need to work with the public to identify solutions.